Trichothecium roseum Link - A new record of hyphomycetous fungus for Bangladesh - Shamsi, Shamim; Sultana, Razia (Bangladesh Journal of Plant Taxonomy, 2008)
Not available. Keywords: Trichothecium roseum; Hyphomycetes; Bangladesh DOI: 10.3329/bjpt.v15i1.932 Bangladesh J. Plant Taxon. 15(1): 77-80, 2008 (June)